Terahertz Spectral Characteristics of Konjac Gum Determined via Microfluidic Technology - Jiang, Huimin; Li, Qingjun; Shen, Yan; Zhou, Hangyu; Li, Yuchai; Su, Bo; Zhang, Cunlin (International Journal of Optics, 2022)
Terahertz radiation enables nondestructive testing of biological samples, but is challenged by its high absorption in aqueous samples, so microfluidic technology is introduced to reduce the absorption. In this study, we designed a special temperature control device and an electric field device for a microfluidic chip to examine the terahertz spectral characteristics of konjac gum at different temperatures, concentrations, and electric field exposure time using the terahertz time domain spectroscopy system. Results demonstrate that higher concentrations of konjac gum lead to higher transmission intensity of terahertz radiation and a lower absorption of the radiation. Higher temperatures of the konjac gum lead to lower terahertz transmittance, and longer exposure time in the electric field leads to a lower transmittance of terahertz radiation and its higher absorption by the konjac gum. At the same time, we explain this phenomenon from the perspective of micromolecules. This study provides technical guidance for the detection of konjac gum by terahertz technology.